A sketch-and-spray interface for modeling trees - S.R.M., Shukri; M.N., Zakaria (2007)

(untitled)
We introduce in this paper an interface for modeling botanical trees that we term a sketch-and-spray interface. In using the interface, a user would sketch out various types of strokes to construct the main structures of a tree. A user could use a branch stroke to draw a single branch, a leaf stroke to draw a single leaf or a stem of leaves, or a copy stroke to draw a whole branch together with all its sub-branches and leaves. A user could also use various editing strokes to modify the tree structure. Finally, a user could spray particles upon it to 'grow' the overall shape of the tree. We illustrate the utility of our interface using a number of examples throughout this paper. Â© Springer-Verlag Berlin Heidelberg 2007.